Conciencia histórica de juventudes mexicanas y su relación con la noción de ciudadanía - Paulina Latapí Escalante; Emma Delfina Rivas Servín (Clio y Asociados, 2023)
The purpose was to elucidate how the interpretation of the past takes action in the notion of citizenship of high school students from Querétaro in relation to the Mexican Republic. A selective quantitative methodology (data from the Americas Barometer Project and Resident Project data) was implemented to interpret them qualitatively. It is exposed a) problematization of the construct of citizenship in relation to historical consciousness and culture; b) comparison of data from the Resident Project for Querétaro (Latapí and Rivas, 2021, 2022), applied to young people aged 16 to 18 in 2019, with national data on 18-year-olds from the Barometer of the Americas, 2021; c) results provide agreement on the concept of depoliticized and static citizenship associated with legalistic rules, not built on participation but on the observance of moral norms. This is associated with the prevailing historical culture and historical consciousness.